STIMULASI UNTUK PERKEMBANGAN MOTORIK HALUS ANAK PRASEKOLAH - Siti Nur Azizah; Ria Setia Sari; Febi Ratnasari (Nusantara Hasana Journal, 2023)
Preschool age is a golden period in children’s fine motor development. At the time a lot of stimulation must be given in order to improve the child’s fine motor skills and prevent delays. Optimal fne motor development will make it easier for children to learn when entering elementary school. Aim: Conduct a review on articles about any stimulation that can improve the development of fine motor skills in preschool children. The method used is a literature review by searching and collecting journals or articles from various source site providers such as SAGE Journal, Researchgate, ProQuest, Google Scholar and Wiley Online Library which were selected with inclusion and exclusion criteria within the journal period 2017-2021. Obtained 11 journals or articles from the collection and selection process which were entered in the synthesis matrix table. Discussion: There are 11 journals or research articles with different stimulations such as research journals about puzzle, brain exercise, drawing, palying lego, finger painting and others. Stimulation given regularly and in various ways has an impact on increasing children’s fine motor development. Stimulation given to children provides opportunities for children to practice their fine motor skills.